Exploring the influence of the geopolitical risks on the natural resource price volatility and correlation: Evidence from DCC-MIDAS-X model - Liu, H.; Yang, P.; He, Y.; Oxley, Leslie; Guo, P. (2024)
This paper uses the expanded dynamic conditional correlation mixed data sampling (DCC-MIDAS-X) model to examine the impact of low-frequency geopolitical risks (GPR) on high-frequency volatility and the correlation of natural resource prices. The empirical results show that GPR and its sub-indices can significantly affect the volatility and correlation of natural resources. The increase in Geopolitical Threats (GPRT) significantly affects the long-run volatility of European Union Allowance (EUA) and Brent crude oil prices. Geopolitical Acts (GPRA) mainly affect the long-run volatility of natural gas prices. In addition, the long-run correlation coefficient, long-run correlation coefficient indicates a competitive relationship between natural resources. Finally, increased GPR and GPRT can significantly reduce the long-run correlation between natural resources. Based on its conclusions, this research makes policy suggestions for businesses and the government. Investors should effectively identify different types of geopolitical risks and their influences to reduce losses and optimize investments. Governments could adjust their policies appropriately to avoid economic shocks due to natural resource volatility caused by geopolitical risks and ensure a stable supply of natural resources.